Characterization of Canine Patients with Heart Disease based on Age at the Pet`a Vet Veterinary Clinic in Guatemala City, Guatemala (Global Journal of Medical Research, 2024)
In this study the clinical records of canine patients seen at the Pet a Vet veterinary clinic in Guatemala between 2018 and 2020 were analyzed with the aim of investigating heart disease in dogs in the region From a total of 1215 records reviewed 825 cases of heart disease were identified with chronic mitral valve disease being the most frequent A higher incidence was observed in males and in Schnauzer breed dogs In addition the majority of diagnosed patients were found to be 9 years of age or older These results provide valuable information on the epidemiology of canine heart disease in Guatemala which may be useful to improve its diagnosis and clinical management
Keywords: canine heart disease; chronic mitral valve disease; dogs; guatemala